2019
DOI: 10.1002/aocs.12212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molecular Structure on the Physical, Chemical, and Electrical Properties of Ester‐Based Transformer Insulating Liquids

Abstract: This article presents the experimental studies carried out on the environmental friendly polyol ester insulating liquids to investigate the effect of molecular structure on the physical, chemical, and electrical properties. Six different polyol esters that can be produced from the transesterification of various methyl esters with neopentylglycol/trimethylolpropane alcohols were synthesized and compared with those of refined, bleached, and deodorized palm oil (RBDPO) and mineral transformer oil. The finding sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…It has been reported that eliminating H atoms on β‐C (i.e. β‐H atom) of triglyceride molecules can effectively improve the thermochemical properties of natural ester molecules [49]. Common synthetic ester insulating oils are hindered esters that lack β‐H.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that eliminating H atoms on β‐C (i.e. β‐H atom) of triglyceride molecules can effectively improve the thermochemical properties of natural ester molecules [49]. Common synthetic ester insulating oils are hindered esters that lack β‐H.…”
Section: Resultsmentioning
confidence: 99%
“…The chain reaction propagates through β‐scission, which leads to C‐C bond decomposition and the formation of large quantities of small unsaturated hydrocarbons. The process of β‐scission of the C‐C bond can also activate the substrate and generate many new free radicals [49]. In addition to β‐scission, which is dominant, conjugated reactions have been observed, which are important because the reactions' products can combine with olefin compounds through Diels‐Alder reactions to produce naphthenic hydrocarbons and aromatic hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…In three reports by our group (Raof et al, 2019b;Raof et al, 2019a;Raof et al, 2019c), the high oleic TMPE was synthesized from palm oil methyl ester. We studied the effect of molecular structure on the physicochemical and electrical properties in detail.…”
Section: Transformer Insulating Liquidmentioning
confidence: 99%
“…The only drawbacks of this ester are its physical properties such as high viscosity and pour point which does not conform to the IEC standard. Thus, in a different study, we blend the TMPE with mineral oil and 80%/20% blend (TMPE/mineral oil) was found to be promising with properties nearest to the standard values for transformer liquid insulation (Raof et al, 2019c). The blend provides significant benefits to utilities in terms of improved fire safety, biodegradability, and performance properties.…”
Section: Transformer Insulating Liquidmentioning
confidence: 99%
“…Phosphoric esters have high fire point and permittivity. In certain aspects, such as breakdown voltage, dissipation factor and resistivity, they are supposed to be comparable or even better than mineral oil, but they tend to also have some negative aspects because they pose some environmental risks [24,41]. Because of the latter, their use is rather limited.…”
Section: Possible Alternatives To Transformer Oimentioning
confidence: 99%